PENGARUH MODEL STUDENT TEAMS ACHIEVEMENT DIVISION TERHADAP HASIL BELAJAR PKn KELAS III SEKOLAH DASAR - Tyas Setia Ningrum; Tahmid Sabri; Endang Uliyanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research aims to know the influence of model Student Teams Achievement Division against the results of studying Civics education III elementary school 35 South of Pontianak. Methods used namely methods of experimentation with the form of a quasi experimental design and form Non equivalent control group design. The population in this research is the whole grade III primary school 35 South Pontianak  totalling 95 people and samples in research is determined by way of a non probality sampling. Data collection techniques used are measurement techniques with data collection tools in the form of a test in the form of multiple choice. Based on the results of the study, the average post-test students in experiments class of 73.32, and   average post-test classes control  of 67.63 two class normal distribution, calculations by t-tests obtained tcount of 2.091 and ttable of 2.000 because tcount > ttable, then Ha received. It can be concluded that there is an influence of the use of the model Student Teams Achievement Division against the results of studying Civics education III elementary school 35 South of Pontianak. Based on the results of the calculation of effect size (ES) obtained ES = 0.50, which included the medium criteria. Keywords :  Civics education, Influence, Learning Outcomes, Student Teams Achievement Division